2022
DOI: 10.1007/s00068-022-01974-3
|View full text |Cite
|
Sign up to set email alerts
|

Orthogeriatric co-management: differences in outcome between major and minor fractures

Abstract: Purpose Literature shows that orthogeriatric co-management improves the outcomes of patients with hip fractures. Corresponding research with more diverse fragility fracture groups is lacking. Therefore, an examination was performed prospectively as a 2 year-follow-up on an orthogeriatric co-managed ward, comparing relevant outcome parameters for major and minor fragility fractures. Methods All patients treated on an orthogeriatric co-managed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Yet, the body of evidence regarding the effectiveness of orthogeriatric co-management models is mainly based on patients with hip fractures [ 25 , 58 , 59 ]. Patients with non-hip fractures could also benefit from orthogeriatric co-management, however, the evidence is limited [ 26 ]. As such, a heterogenous population consisting of community-dwelling and non-community-dwelling patients with all types of major osteoporotic fractures will be included in the G-COMAN intervention and the evaluation in the G-COMAN Fractures study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, the body of evidence regarding the effectiveness of orthogeriatric co-management models is mainly based on patients with hip fractures [ 25 , 58 , 59 ]. Patients with non-hip fractures could also benefit from orthogeriatric co-management, however, the evidence is limited [ 26 ]. As such, a heterogenous population consisting of community-dwelling and non-community-dwelling patients with all types of major osteoporotic fractures will be included in the G-COMAN intervention and the evaluation in the G-COMAN Fractures study.…”
Section: Discussionmentioning
confidence: 99%
“…Geriatric-surgical co-management models for surgical patients (i.e., orthopedic surgery, gastro-intestinal surgery, and an acute surgery unit) have shown a beneficial impact on length of stay, mortality, and hospital readmission rates [ 24 ]. Moreover, evidence revealed that geriatric patients with all types of osteoporotic fractures could improve from orthogeriatric co-management [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hip fractures clearly dominating the scientific discourse [ 11 ], but fragility fractures occur in multiple parts of the human body, such as humerus, pelvis, spine or wrist [ 12 ] and often precede devastating hip fractures [ 13 ]. Data on orthogeriatric care in the course of different fragility fractures is poor [ 14 ]. Here, we hypothesize that not only hip fracture patient benefit from orthogeriatric care.…”
Section: Introductionmentioning
confidence: 99%
“…The recovery of the daily living ability and optimal management of potential comorbidities is the central aim in the treatment of osteoporotic indicator fractures in the aging patient. Overall functional rehabilitation represents an important evaluation criterion in geriatric traumatology [4]. Because of socioeconomic considerations, possible prevention of long-term care dependency and due to the ethical assignment of a surgeon, it is particularly necessary to analyze our care strategies to regular quality assuring data analysis.…”
Section: Introductionmentioning
confidence: 99%